Effect of Water-to-Binder Ratio on Density, Compressive Strength and Morphology of Fly Ash/Ladle Furnace Slag Blended One-Part Geopolymer - H. Yong-Jie; H. Cheng-Yong; M.M.A.B. Abdullah; L. Yeng-Seng; O. Shee-Ween; O. Wan-En; L. Jia-Ni; T. Hoe-Woon (Archives of Metallurgy and Materials)
Water-to-binder (W/B) ratio has a great influence on the bulk density, compressive strength and morphology of fly ash/ladle furnace slag (FA/LFS) blended one-part geopolymer. The objective of this work is to evaluate the effect of W/B ratio on the performance of the one-part geopolymer. The one-part geopolymer were prepared at W/B ratio of 0.20-0.30 and cured at room temperature for 28 days. The bulk density, water absorption, apparent porosity and compressive strength were determined, while the morphology was examined by scanning electron microscopy (SEM). The results showed that the one-part geopolymer with W/B ratio of 0.25 had highest compressive strength (39 MPa) with denser (2.1 g/cm3) structure as well as low water absorption (3.97%) and low apparent porosity (8.33%). The micrograph showed the optimal one-part geopolymer has less agglomeration of FA and LFS particles.